Upon the 75th Anniversary of the Psychoanalytic Study of the Child. Issue 1 (31st December 2022) - Lament, Claudia
ABSTRACT: As the outgoing editor-in-chief of The Psychoanalytic Study of the Child, I offer my reflections upon the seventy-fifth volume as I look back at the inception of the series in 1945, and my impressions about then and now. While there are most certainly remarkable differences in the zeitgeist, both in terms of culture, the larger social polity, and shifts in psychoanalytic interests, there are also similarities between these two eras which link them in surprising ways.